Gastro-oesophageal reflux is not a major cause of brief resolved unexplained events in infants - Jilani, Nadeem Z. (Breathe (Sheff), 2019)
Although it is often stated that gastro-oesophageal reflux is the most common cause of a brief resolved unexplained event or apparent life-threatening event, there are very few data to support the hypothesis of cause and effect http://bit.ly/2FjknUy